2020
DOI: 10.3390/ijerph17020629
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Spatio-Temporal Analysis of Urban Expansion and Pollutant Emissions in Fujian Province

Abstract: Urbanization processes at both global and regional scales are taking place at an unprecedent pace, leading to more than half of the global population living in urbanized areas. This process could exert grand challenges on the human living environment. With the proliferation of remote sensing and satellite data being used in social and environmental studies, fine spatial- and temporal-resolution measures of urban expansion and environmental quality are increasingly available. This, in turn, offers great opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…A large number of empirical studies have demonstrated the relationships between pollutant emissions, urbanization, and economic development [ 18 , 19 , 20 , 21 , 22 ]. However, these studies rarely focus on the sources of PM 2.5 emissions to explain the differences in correlations between these variables and urban expansion.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of empirical studies have demonstrated the relationships between pollutant emissions, urbanization, and economic development [ 18 , 19 , 20 , 21 , 22 ]. However, these studies rarely focus on the sources of PM 2.5 emissions to explain the differences in correlations between these variables and urban expansion.…”
Section: Introductionmentioning
confidence: 99%
“…The resource depletion and environmental pollution [1][2][3][4][5] caused by the rapid development of modern society and economy are becoming more and more serious and have been identified as global public health issues [6]. Water, the basis of all life and an indispensable and irreplaceable element of natural resources and environment for social and economic development, is often not accessible for approximately 11% of the world's population [7].…”
Section: Introductionmentioning
confidence: 99%